2019
DOI: 10.3389/fmicb.2019.00362
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Bioinformatics Workflow for Routine Analysis of Whole-Genome Sequencing Data and Related Challenges for Pathogen Typing in a European National Reference Center: Neisseria meningitidis as a Proof-of-Concept

Abstract: Despite being a well-established research method, the use of whole-genome sequencing (WGS) for routine molecular typing and pathogen characterization remains a substantial challenge due to the required bioinformatics resources and/or expertise. Moreover, many national reference laboratories and centers, as well as other laboratories working under a quality system, require extensive validation to demonstrate that employed methods are “fit-for-purpose” and provide high-quality results. A harmonized framework wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 60 publications
1
65
0
Order By: Relevance
“…We performed genotypic resistance gene detection, as described by Bogaerts et al (23), against the Res-Finder database (24). We defined AMR gene clusters as resistance genes on the same contig within a sample.…”
Section: Antimicrobial-resistance Genotypingmentioning
confidence: 99%
“…We performed genotypic resistance gene detection, as described by Bogaerts et al (23), against the Res-Finder database (24). We defined AMR gene clusters as resistance genes on the same contig within a sample.…”
Section: Antimicrobial-resistance Genotypingmentioning
confidence: 99%
“…Although, there are many tools available to analyze NGS results, many of these require substantial bioinformatic expertise because they are only available using the command line on Linux. Therefore, the spread of more web-based platforms with a user-friendly interface within the scientific community would be an advance in the use of WGS for non-bioinformatic experts [60].…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Classical subtyping data were provided by the NRC and determined as described by Bertrand et al (2011). Designation of antigen gene alleles for porA, porB, and fetA genes were obtained with the Neisseria pipeline described by Bogaerts et al (2019), by comparing assembled sequencing data to reference alleles downloaded from the Neisseria PubMLST 1 database (Jolley et al, 2018).…”
Section: Isolates Genomic Dna Extraction and Sequencing Data Acquisimentioning
confidence: 99%
“…ND, not determined; NT, non-serotypeable; NST, non-serosubtypeable; NE, clonal complex does not exist. Clonal complex (cc), sequence type (ST), PorB VR, PorA VR1, PorA VR2, and FetA determined in silico as described in Bogaerts et al (2019), Serogroup:serotype:serosubtype determined in vitro as described in Bertrand et al (2011). In Bertrand et al (2011), isolate 2008-114 was identified as ST2592.…”
Section: Reference Genomesmentioning
confidence: 99%
See 1 more Smart Citation